Development and application of UAV-SfM photogrammetry for quantitative characterization of rock mass discontinuities. (May 2021) - Kong, Deheng; Saroglou, Charalampos; Wu, Faquan; Sha, Peng; Li, Bo
Abstract: Remote sensing techniques (e.g., terrestrial laser scanning and digital photogrammetry) have been developed and applied rapidly in recent years for identification and analysis of rock mass characteristics. A direct validation of these digital measurements against well-constrained datasets obtained from conventional survey methods is reported here. A high-resolution digital outcrop model (DOM) generation method for rock exposures based on unmanned aerial vehicle (UAV) photogrammetry integrated with a structure from-motion (SfM) technique was introduced. A digital procedure based on mathematical algorithms for discontinuity detection, trace mapping and quantitative discontinuity characterization was established. The proposed method was applied to two rock slopes (from Greece and China) and fundamental discontinuity parameters, i.e., the orientation, number of sets, trace length, set spacing, linear frequency, areal frequency and areal intensity were statistically extracted and calculated. Their values were compared with carefully planned manual measurements, i.e., individual discontinuity measurements, scanline method, and window sampling method on the same sites. The results of two sites showed that most deviations are less than 5° for dip direction and dip angle, 0.13 m for exposed discontinuity length, 0.37 m for set spacing, 0.09 m -1 for linear frequency, 0.06 m -2 for areal frequency, and 0.15 m -1 for areal intensity. These deviations are reasonable and acceptable, which confirmed the reliability and accuracy of the developed method. With improved efficiency and workability comparing to conventional methods especially in difficult surveying environments, the UAV-SfM Photogrammetry can potentially become a routine method for on-site rock mass characterization. Highlights: A digital outcrop model generation method for rock exposures based on UAV-SfM photogrammetry was developed. A procedure for discontinuity detection, digital trace mapping and discontinuity characterization was established. Fundamental discontinuity parameters of two rock slopes were statistically extracted and analyzed. Quantitative comparisons between the results obtained from digital and conventional methods were presented.